Diet patterns associated with cognitive decline: methods to harmonize data from European and US cohort studies - Ayala-Garcia, Amaia; Soldevila-Domenech, Natalia; Yi, So-Yun; de la Torre, Rafael; Steffen, Lyn M.; , for the IAFNS Retrospective Harmonization Expert Working Group; Blackwell, Courtney K.; Khoo, Christina; Mansolf, Maxwell Armand; Ros, Emilio; Snetselaar, Linda; Wey, Tina (Frontiers in Nutrition, 2024)
The impact of dietary intake on cognitive outcomes and dementia prevention is a topic of increasing interest. Meta-analyses of observational studies, mostly conducted within US and European populations, have reported benefits of healthy diet patterns on cognitive performance, but results from individual studies have been inconsistent. These inconsistencies are likely due to the diverse methodology used in studies, including different diet and cognitive function assessment instruments, follow-up periods, and analytical methods, which make drawing conclusions relevant to dietary guidance challenging. The objective of this project is to describe a protocol to conduct a retrospective harmonization study on dietary intake and cognitive health using data from European and US studies. The recommendations resulting from the project can be used to support evidence-based synthesis for future iterations of the Dietary Guidelines for Americans or other population-based dietary guidance. Additionally, this study will serve as a harmonization guide for future research on the relationship between diet patterns and cognition. The approach outlined ultimately aims to optimize resources and expedite research efforts for dementia prevention.